How outdoor and indoor green spaces affect human health: a literature review - Paniccià, Marco; Acito, Mattia; Grappasonni, Iolanda (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The analysis of the complex interactions between outdoor or indoor greenness and the health of individuals and ecosystems is a topic of current and growing interest. Study design. This review aims to examine and summarise the results of studies conducted to evaluate the effects of exposure to greenness on various aspects of human health and the natural environment. Methods. For this purpose, in April 2024 we searched PubMed, Web of Science, and Scopus databases, Google Scholar and specialised books. Results. Evidence gathered demonstrates a remarkable correlation between exposure to outdoor and indoor greenness and the improvement of mental health, including the reduction of stress, anxiety, and depression. Contact with greenness is also associated with improvements in physical health, such as reductions in blood pressure, heart rate, and inflammation, as well as in cognitive abilities, concentration, and overall recovery. These benefits are recognisable both in outdoor spaces, such as urban parks, oases, and public gardens, and in indoor spaces, through the introduction of plants and nature-evoking elements in living and working environments. The presence of vegetation in indoor environments, such as offices, schools, healthcare facilities, prisons, and others, can contribute to improving the quality of social spaces, fostering communication, and collaboration, and attenuating aggressiveness and inequalities, thereby increasing employee satisfaction and work efficiency. The combination of outdoor/indoor green spaces and the well-being of the living environment includes exposure to greater biodiversity, mitigation of extreme weather events, absorption of atmospheric pollutants, attenuation of urban background noise, and increased privacy. The presence of vegetation in urban areas has a positive impact on social cohesion, promoting interpersonal interaction and facilitating the development of more cohesive and inclusive communities, thus supporting a sense of belonging and collective identity. Conclusions. In conclusion, these results underline the importance of considering contact with greenness as a fundamental element in promoting the psychophysical health and well-being of individuals and ecosystems, suggesting the adoption of nature-based therapies and interventions in public health policies and urban planning practices.